2013
DOI: 10.1039/c3md00085k
|View full text |Cite
|
Sign up to set email alerts
|

Design of potential bisubstrate inhibitors against Mycobacterium tuberculosis (Mtb) 1-deoxy-d-xylulose 5-phosphate reductoisomerase (Dxr)—evidence of a novel binding mode

Abstract: In most bacteria, the nonmevalonate pathway is used to synthesize isoprene units. Dxr, the second step in the pathway, catalyzes the NADPH-dependent reductive isomerization of 1-deoxy-D-xylulose-5-phosphate (DXP) to 2-C-methyl-D-erythritol-4-phosphate (MEP). Dxr is inhibited by natural products fosmidomycin and FR900098, which bind in the DXP binding site. These compounds, while potent inhibitors of Dxr, lack whole cell activity against Mycobacterium tuberculosis (Mtb) due to their polarity. Our goal was to us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 38 publications
0
49
0
Order By: Relevance
“…Each compound was designed from resolved crystal structures of M. tuberculosis MEP synthase in complex with fosmidomycin [33] [34] and contains an amide-linked or O-linked functional group.…”
Section: Methodsmentioning
confidence: 99%
“…Each compound was designed from resolved crystal structures of M. tuberculosis MEP synthase in complex with fosmidomycin [33] [34] and contains an amide-linked or O-linked functional group.…”
Section: Methodsmentioning
confidence: 99%
“…This can be ascribed to the Cd → Zn substitution in the obtained nanophotocatalysts. In addition, from Figure 4, the Raman intensities of 1-LO and 2-LO are both relatively strong and narrow, which implies its good crystallinity and ordered structure [28]. …”
Section: Resultsmentioning
confidence: 99%
“…(8) An interesting conclusion from this work pertained to the importance of the retrohydroxamate in Dxr inhibition. The retrohydroxamate, found in fosmidomycin, FR900098, and most Dxr inhibitors reported to date, is expected to coordinate a divalent cation resident between the DXP and NADPH binding sites.…”
mentioning
confidence: 77%
“…(3234) Recently, we explored a bisubstrate approach where compounds were designed to occupy both the DXP and NADPH binding sites. (8) These compounds stem from two structure classes: an N -acyl series includes extensions of fosmidomycin’s formyl group, and an O -linked series explores substitution of the hydroxyl group of the retrohydroxamate (Figure 2). Early modeling efforts suggested that compounds from both series would act as Dxr ligands.…”
mentioning
confidence: 99%
See 1 more Smart Citation